Single Axis Passive Solar Tracker Performance Evaluation (University of Khartoum Engineering Journal, 2022)
A passive solar tracker was designed and constructed in GIAD Industrial Complex. The tracker was tested in Soba region, in the premises of the National Energy Research Center. The test consisted of two parts; the first was testing the tracking error by placing a pyranometer on the tracker and comparing the beam radiation readings with that of the maximum theoretical beam radiation possible if the tracker was tracking without errors. The second test was comparing the power output of 8, 50Wp photovoltaic modules attached onto the tracker in tracking mode to the same modules on the tracker fixed in a straight position. The array is inclined to 15.5o facing South. The results showed that most of the tracking error was within the range of 7.37 %. The photovoltaic array comparison test showed that the tracker is most effective in the morning hours from 9:00 to 11:00 and in the afternoon from 15:00 to 17:00. The increase of power output of the tracked array to the fixed array was 12.67% on the day of 9thDecember and 14.39% on the day of 11thApril.
Keywords: Solar energy; Passive solar tracker; Photovoltaic modules; Pyranometer